Respiratory exposure to graphene quantum dots causes fibrotic effects on lung, liver and kidney of mice. (May 2022) - Wu, Tianshu; Wang, Xinyu; Chen, Min; Zhang, Xiaomeng; Zhang, Jixiang; Cheng, Jin; Kong, Lu; Tang, Meng
Abstract: Graphene quantum dots (GQDs), as a novel graphene-based nanoparticle, presented a bright prospect in fields of biomedicine due to their excellent optical property. However, the biosafety assessment of GQDs is far behind their rapid development, which could restrict their wilder applications. This study focused on the potential adverse effects of two kinds of promising GQDs, i.e. nitrogen-doping graphene quantum dots (N-GQDs) and amino-modified graphene quantum dot (A-GQDs) on primary target organs of GNMs, including lung, liver and kidney. The intranasal instillation used here was to imitate the respiratory exposure of GQDs that is a commonly exposure route of GQDs in the environment. Although no severe damages associated with general health occurred in mice treated with GQDs, the fibrosis evidenced by statistically significant increases in the area of collagen I and TGF-ß1 and p-Smad3 expressions were observed in the lung, liver and kidney tissues. Interestingly, the fibrotic effect induced by GQDs could be effectively alleviated by a ferroptosis-specific inhibitor, which demonstrated a close relationship of fibrosis and ferroptosis. This study not only provides new insights on the toxicity mechanisms of GQDs, but also offers some efficient ways to control toxicity of GQDs, like dosage threshold and small molecular drugs. Graphical abstract: Image 1